Review of the monograph by Salikhova L.B. "Municipal government in Dagestan during the second half of XIX - early XX century". Makhachkala: "Alef", 2014. - 236 p - Dalgat, E M (History, Archeology and Ethnography of the Caucasus, 2016)
-